Rotavirus Vaccine Is Effective Against Rotavirus Gastroenteritis Resulting in Outpatient Care: Results From the Medically Attended Acute Gastroenteritis (MAAGE) Study. (23rd April 2020) - Burke, Rachel M; Groom, Holly C; Naleway, Allison L; Katz, Eric M; Salas, Bianca; Mattison, Claire P; Donald, Judy; Tsaknaridis, Laura; Biggs, Christianne; Bowen, Michael D; Tate, Jacqueline E; Parashar, Umesh D; et al.
Abstract: Background: Rotavirus is a common cause of severe pediatric acute gastroenteritis. Two vaccines are licensed in the United States and have demonstrated high effectiveness against moderate to severe disease. However, fewer data are available on rotavirus vaccine effectiveness (VE) against milder disease. Methods: We leveraged active surveillance data from Kaiser Permanente Northwest to calculate rotavirus VE against medically attended rotavirus illness among age-eligible children. We utilized a test-negative case-control design and applied 4 distinct case definitions based on reverse transcription–quantitative real-time PCR (qRT-PCR) assay and enzyme immunoassay (EIA) test results. VE was calculated as 100 × (1 − odds ratio), and models were adjusted for age group. Results: The VE analysis population comprised 842 children, 799 (95%) of whom had mild disease requiring at most a clinic visit and 698 (83%) of whom were fully vaccinated against rotavirus. Age-adjusted VE was 70% (95% confidence interval [CI], 37–86%) against disease defined solely by qRT-PCR results, 72% (95% CI, 31–89%) against disease as defined by qRT-PCR with a quantification cycle ( C q ) value <27, 73% (95% CI, 32–90%) against disease that was qRT-PCR positive but EIA negative, and 62% (95% CI, –20–88%) against disease defined solely by EIA. Results were similar when restricting to disease resulting in at most an ambulatory clinic or emergency department visit. Conclusions: These results support the effectiveness of rotavirus vaccination in protecting US children from mild to moderate and severe disease. Our findings are also useful to show the effectiveness of rotavirus vaccination against qRT-PCR–defined illness. Abstract : Using active surveillance data from Kaiser Permanente Northwest, we estimated that rotavirus vaccine was 70% (95% confidence interval, , 37–86%) effective against medically attended rotavirus gastroenteritis of any severity. Findings were similar for disease resulting in, at most, outpatient care.